1983
DOI: 10.1148/radiology.146.3.6572408
|View full text |Cite
|
Sign up to set email alerts
|

Radiation absorbed-dose estimates for the liver, spleen, and metaphyseal growth complexes in children undergoing gallium-67 citrate scanning.

Abstract: Quantitative conjugate-view external counting techniques were applied to estimate the radiation dose to the liver, spleen, and metaphyseal growth complexes (distal femur and proximal tibia) for ten pediatric patients undergoing gallium-67 scanning procedures. The effective half-life of Ga 67 in these organs was approximately 78 hours. The dose per unit of administered activity for the liver and spleen was between 0.3 and 4.0 rad/mCi (0.08 to 1.08 Gy/GBq) and 0.5 and 7.0 rad/mCi (0.13 to 1.89 Gy/GBq), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…15,16 In order to correct for attenuation without a knowledge of source depth, the conjugate-view method requires only the bodythickness or transmission data using an external source. [4][5][6][7][8][9][10] Macey et al 4 reported a transmission-emission method using a gamma camera and an external uniformity source for the absolute quantitation of Tc-99m in the lungs in clinical studies. Malko et al 5 also proposed a simple conjugate-view method using an external flood source to determine the volume of small or medium size sources ͑Ͻ8 cm͒.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 In order to correct for attenuation without a knowledge of source depth, the conjugate-view method requires only the bodythickness or transmission data using an external source. [4][5][6][7][8][9][10] Macey et al 4 reported a transmission-emission method using a gamma camera and an external uniformity source for the absolute quantitation of Tc-99m in the lungs in clinical studies. Malko et al 5 also proposed a simple conjugate-view method using an external flood source to determine the volume of small or medium size sources ͑Ͻ8 cm͒.…”
Section: Discussionmentioning
confidence: 99%
“…The background count rates equivalent to the source volume, CBGao and CBGbo observed with the camera heads A and B, respectively, are derived as described in Ref. 10. Equations ͑B1͒ and ͑B2͒ are corrected for oversubtraction by CaЈϪCBGaϩCBGaoϭATa•ATc•SA•Co, ͑B5͒…”
Section: B Background Correction Technique Using the Source Depth (Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of this topic in recent decades have developed many theoretical simulations of the cumulative dose of radioactive nuclides since each nuclide has a unique radioactive fingerprint. Although most theoretical studies of this issue have applied the medical internal radiation dose (MIRD) calculation model, their conclusions are highly variable [110]. Practical studies of internal dose are rarely performed and their results are even more inconsistent [11–15].…”
Section: Introductionmentioning
confidence: 99%
“…Absolute measurement of the activity in an organ, in both planar and tomographic examinations, also implies a determination of effective depths and effective attenuation coefficients. The attenuation correction should consider both the thickness of the organ and the depth of the organ in the body as with the conjugate view method (Fleming 1979, Macey and Marshall 1982, Thomas et al 1983. The conjugate view method uses the geometric mean from two opposing views together with the system calibration factor and a correction factor for source attenuation and source thickness where the effective total linear attenuation coefficient across the source is used.…”
Section: Introductionmentioning
confidence: 99%